1994
DOI: 10.1128/aac.38.9.2101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enteral feeding with ensure on oral bioavailabilities of ofloxacin and ciprofloxacin

Abstract: The relative oral bioavailabilities of ciprofloxacin and ofloxacin when they were coadministered with water or an enteral feeding product (Ensure) were assessed in 13 healthy volunteers. The area under the concentration time curve from time zero to infinity and the maximum concentration of drug in serum for both drugs were reduced by Ensure in comparison with those by water (P < 0.01). However, Ensure reduced the percent relative bioavailability of ciprofloxacin (72% ± 14%; range, 52 to 96%) significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 37 publications
1
28
0
2
Order By: Relevance
“…The sample size was estimated to provide 80% power to detect a 35% difference in bioavailability of oral linezolid between patients receiving continuous EF and controls (␣ ϭ 0.05; two-tailed), assuming 100% bioavailability in the control subjects with a coefficient of variation of 20% (18). The percent difference in bioavailability of 35% was deemed clinically significant and is similar in magnitude to the difference observed with other antibiotics when administered with continuous enteral feedings in hospitalized patients (4,10).…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was estimated to provide 80% power to detect a 35% difference in bioavailability of oral linezolid between patients receiving continuous EF and controls (␣ ϭ 0.05; two-tailed), assuming 100% bioavailability in the control subjects with a coefficient of variation of 20% (18). The percent difference in bioavailability of 35% was deemed clinically significant and is similar in magnitude to the difference observed with other antibiotics when administered with continuous enteral feedings in hospitalized patients (4,10).…”
Section: Methodsmentioning
confidence: 99%
“…Concurrent administration of Ensure ® enteral feeding significantly reduced single-dose ciprofloxacin and ofloxacin bioavailability as assessed using C max (mean −47 and −36%, respectively) and AUC (mean −27 and −10%, respectively) data. However, the extent of the interaction was significantly greater for ciprofloxacin than for ofloxacin [109].…”
Section: Absorption Interactionsmentioning
confidence: 90%
“…Antibacterial quinolones, such as ciprofloxacine and ofloxacine, are well absorbed orally, a fact suggesting a similar behaviour following administration by nasogastric tube. Yet a decreased absorption following administration by the latter route was demonstrated for ciprofloxacine and ofloxacine [18]. Another study also found significant losses for ciprofloxacine, ofloxacine and levofloxacine when these were mixed with an enteral feeding formulation [19], suggesting that the phenomenon was a characteristic of this whole class of drugs.…”
Section: Introductionmentioning
confidence: 97%